2017
DOI: 10.1039/c7dt02002c
|View full text |Cite
|
Sign up to set email alerts
|

Ligand effect on the rhodium porphyrin catalyzed hydrogenation of [2.2]paracyclophane with water: key bimetallic hydrogenation

Abstract: Rhodium porphyrin catalyzed hydrogenation of the aliphatic carbon-carbon σ-bond of [2.2]paracyclophane with water has been examined with a variety of tetraarylporphyrins and axial ligands. Mechanistic investigations show that Rh(ttp)H, which can be derived from the reaction of [Rh(ttp)] with water without a sacrificial reductant, plays an important role in promoting bimetallic reductive elimination to give the hydrogenation product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 66 publications
2
0
0
Order By: Relevance
“…Protonation of the Rh I complex 2 by CF 3 SO 3 H results in the formation of the dinuclear Rh II complex [Rh II 2 (iMP) 2 (CH 3 CN) 4 ]­(PF 6 ) 4 ([ 3 ]­(PF 6 ) 4 , iMP = 2,6-bis­(2-imidazolyl-1-methyl)­pyridine) with evolution of H 2 through the detectable hydride intermediate [Rh III (iMP)­(H)­(CH 3 CN) 2 ] 2+ ( A ) (Scheme ). , We could not isolate the hydride intermediate A because unstable A gradually transforms into the dinuclear Rh II complex 3 with generation of H 2 . It was confirmed that the yield of evolved H 2 corresponds to that of formed 3 .…”
Section: Resultssupporting
confidence: 82%
“…Protonation of the Rh I complex 2 by CF 3 SO 3 H results in the formation of the dinuclear Rh II complex [Rh II 2 (iMP) 2 (CH 3 CN) 4 ]­(PF 6 ) 4 ([ 3 ]­(PF 6 ) 4 , iMP = 2,6-bis­(2-imidazolyl-1-methyl)­pyridine) with evolution of H 2 through the detectable hydride intermediate [Rh III (iMP)­(H)­(CH 3 CN) 2 ] 2+ ( A ) (Scheme ). , We could not isolate the hydride intermediate A because unstable A gradually transforms into the dinuclear Rh II complex 3 with generation of H 2 . It was confirmed that the yield of evolved H 2 corresponds to that of formed 3 .…”
Section: Resultssupporting
confidence: 82%
“…On the basis of the above results and established mechanisms for rhodium porphyrin metalloradical mediated C–C bond activation of cyclopropanes and cyclooctane, Scheme depicts a plausible mechanism. Rh­(ttp)­Me undergoes alcoholysis with i PrOH to give the reactive Rh­(ttp)­H as well as methane and acetone rapidly, analogous to the reported hydrolysis process with water . The rhodium porphyrin mediated dehydrogenation of i PrOH to form acetone has also been reported previously .…”
Section: Resultssupporting
confidence: 71%